2020
DOI: 10.1002/term.3026
|View full text |Cite
|
Sign up to set email alerts
|

A proof of concept gene‐activated titanium surface for oral implantology applications

Abstract: Dental implants are very successful medical devices, yet implant failures do occur due to biological and mechanical complications. Peri-implantitis is one such biological complication that is primarily caused by bacteria and their products at the implant soft tissue interface. Bacterial infiltration can be prevented by the formation of a reliable soft tissue seal encircling dental implants. Platelet-derived growth factor-BB (PDGF-BB) has significant chemotactic and proliferative effects on various mesenchymal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Despite the benefits of enhanced soft tissue attachment on implant surfaces, such a healing process inevitably takes time: typically around 6–8 weeks for dental implants . Thus, dental implants would benefit from a second defense other than enhanced soft tissue healing during early implant healing, a period in which the implant is most vulnerable to biofilm formation. Due to their microbial resistance, an attractive biomolecule to combat biofilm formation is antimicrobial peptides .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the benefits of enhanced soft tissue attachment on implant surfaces, such a healing process inevitably takes time: typically around 6–8 weeks for dental implants . Thus, dental implants would benefit from a second defense other than enhanced soft tissue healing during early implant healing, a period in which the implant is most vulnerable to biofilm formation. Due to their microbial resistance, an attractive biomolecule to combat biofilm formation is antimicrobial peptides .…”
Section: Introductionmentioning
confidence: 99%
“…According to An et al [32], hydrophilic rough surfaces improve epithelial cell proliferation compared with polished surfaces. In contrast, lower protein expressions of rat oral epithelial cells grown, lower cell attachment, migration, and proliferation were noted on the rough surface compared with smooth surfaces [33] Taking the surface roughness of dental implants and their components into the spotlight, it is worth identifying an optimal implant surface that decreases bacterial attachment and improves mucosal tissue attachment, which remains in debate [12,34,35]. Although previous systematic reviews [3,36] have shown no influence of surface topography on periimplant bleeding on probing-which might argue no effect on bacterial attachment-and on peri-implant soft tissue healing, inflammation, and maintenance, such data should be taken with caution.…”
Section: Discussionmentioning
confidence: 99%
“…The final delivery platform was one targeted to its application and specific RNAs of interest. Tissue engineering strategies such as protein therapy, gene therapy, cell therapy, and their combinations are currently being explored for oral- and craniofacial regeneration and repair. Bone tissue engineering strategies typically involve the use of recombinant proteins such as rhBMP-2 (protein therapy), cells (cell therapy), gene-encoding growth factors and morphogens, biomimetic scaffolds, and their combinations. For example, the Salem lab successfully demonstrated the application of a nonviral gene-based delivery system to enhance bone regeneration. , They employed a gene-activated matrix (GAM) consisting of collagen containing nanoplexes of polyethylenimine (PEI) complexed with plasmid DNA encoding platelet-derived growth factor-BB. They demonstrated superior bone regeneration capacity of GAM in calvarial defects in rats.…”
Section: Modes Of Delivery For Therapeutic Nucleic Acids and Rna Nano...mentioning
confidence: 99%